Web-based learning : men & machines : proceedings of the first International Conference on Web-Based Learning in China, ICWL, 2002, Hong Kong, 17-19 August 2002 (World Scientific, 2002)
This book provides an up-to-date study of technical, pedagogical and managerial issues in Web-based learning. The successful application of Web-based learning provides enhancements in workforce performance, helps to lower costs, and encourages innovation for Web-based and distance learning. It presents a selection of 20 refereed papers given at the First International Conference on Web-Based Learning from over 70 submissions by academic researchers and industry developers from 19 different countries. It provides an excellent resource for students, researchers and practitioners involved in We.